Differences in patterns of physical participation in recreational activities between children with and without intellectual and developmental disability. (August 2017) - Chien, Chi-Wen; Rodger, Sylvia; Copley, Jodie
Highlights: Children with IDD engage physically in most recreational activities. Children with IDD participate less frequently in physical activities. Children with IDD require more assistance during recreational participation. Parents want their child with IDD to participate with less assistance. Abstract: Background: Children with intellectual and developmental disability (IDD) are at risk of experiencing limited participation in recreational activities, where they may be present but not physically engaged. Aim: To compare patterns of physical engagement in recreational activities between children with and without IDD. Methods and procedures: Fifty children with IDD (26 boys, 24 girls; mean age 8.7 years) were matched for age and sex with 50 typically developing children. Parents completed a questionnaire which captured participation in 11 recreational activities involving hand use as an indication of physical engagement. Outcome and results: More than 80% of children in both groups participated physically in eight recreational activities, but fewer children with IDD participated in six activities when compared with typically developing children. Children with IDD also participated less frequently in five activities and required more assistance to participate in all the 11 activities. Parents wanted their child with IDD to participate in 10 recreational activities with less assistance. Conclusions and implications: The difference between the groups related to participation frequency, independence, and parents' desire for changes in their child's participation. Greater efforts are needed to address these differences and to support recreational participation in children with IDD.